Effect of Adhesive Spreading Rate on the Performance of Laminated Compressed Oil Palm Trunks - Noor Afeefah, Nordin; Othman, Sulaiman; Rokiah, Hashim; Nurjannah, Salim; Mohammed, Nasir; Masatoshi, Sato; Salim, Hiziroglu (North Carolina State University, 2015)
The large availability and cheap price of oil palm (Elaeis guineensis) trunk makes it an attractive raw material for value-added applications, but its low density and high carbohydrate content are highly undesirable. In this work, oil palm trunk (OPT) was steam-pretreated and compressed at high temperature. The compressed OPT was laminated using polyvinyl acetate (PVAc) using either 250 or 500 g/m2 adhesive spread rate (ASR). Soil burial testing was performed for three months on two different samples to study the deterioration and weight loss by bio-organisms. The laminated, compressed OPT formed with high PVAc ASR was found to be more durable against bio-organisms. The thermal stability of the compressed OPT was studied by thermogravimetric analysis (TGA), and it was observed that the weight loss was lower for steam-pretreated samples compared to those without steam pretreatment. Moisture absorption-desorption testing of compressed OPT was performed, and a hysteresis curve was generated. It was found that laminated, compressed OPTs with 500 g/m2 ASR had lower moisture absorption than those with 250 g/m2 ASR.